The value of second-line anti-HER2 therapy in metastatic HER-2 positive patients: a cost-effectiveness analysis in China - Li, Lu; Yang, Shilei; Fang, Fengqi; Tian, Li; He, Ying; Li, Jia; Chen, Yanwei; Dong, Deshi (Frontiers in Pharmacology, 2024)
Background: Breast cancer (BC) is one of the most common cancers worldwide. The inevitability of drug resistance to initial anti-HER-2 therapy necessitates the emergence of second-line anti-HER-2 drugs which exhibit a promising outlook. Consequently, it is imperative to appraise their efficacy through network meta-analysis and ascertain their comparative cost-effectiveness.The data used in our analysis were acquired from patients enrolled in the EMILIA, DESTINY-Breast03, and PHOEBE phase III randomized clinical trials. A partitioned survival model was used for patients diagnosed with HER-2-positive metastatic BC. The model was crafted with a time horizon of 10 years, operating on a 21-day cycle and incorporating a 5% discount rate for both costs and outcomes. The willingness-to-pay (WTP) threshold was set at 36,058.06 per qualityadjusted life year (QALY). The impact of parameter uncertainty on the findings was assessed using a one-way deterministic sensitivity analysis and probability sensitivity analysis.Findings: Within the model encompassing 1782 patients, the utilization of pyrotinib plus capecitabine (PC) treatment yielded an additional 0.70 QALY in comparison to T-DM1, resulting in an incremental cost-effectiveness ratio (ICER) of 31,121.53 per QALY gained. Similarly, the administration of T-DXd treatment led to an additional 0.80 QALY compared to T-DM1, resulting in an ICER of 153,950.19 per QALY gained. The PC strategies are considered more cost-effective than T-DXd when the WTP threshold is set at 36,058.06 per QALY. However, this method is not cost effective for T-DXd. The probability of the PC strategies being cost-effective was 62%, whereas the probability of T-DXd was 0% when compared to T-DM1.PC is a cost-effective therapy for patients afflicted with HER-2-positive metastatic BC compared to T-DM1 from the perspective of China at a WTP threshold of 36,058.06 per QALY. Nevertheless, T-DXd is not as cost-effective as T-DM1, considering its current medication pricing. Therefore, reducing the cost of T-DXd could improve its overall cost-effectiveness.